Converting closed mines into giant batteries: Effects of cyclic loading on the geomechanical performance of underground compressed air energy storage systems. (December 2020) - Schmidt, Falko; Menéndez, Javier; Konietzky, Heinz; Pascual-Muñoz, P.; Castro, Jorge; Loredo, Jorge; Sánchez, Antonio Bernardo
Highlights: The feasibility of CAES systems was investigated in a coal mine at 450 m depth. 3D numerical models were performed to simulate the operating conditions. Deformations and plasticity states were analyzed at 5, 7.5 and 10 MPa. The cyclic loading operation was simulated for 10, 000 cycles. An increase of the initial volume of less than 0.5% was observed. Abstract: There are more than one million abandoned mines around the world. A large number of voids from closed mines are proposed as pressurized air reservoirs for energy storage systems. A network of tunnels from an underground coal mine in northern Spain at 450 m depth has been selected as a case study to investigate the technical feasibility of adiabatic compressed air energy storage (A-CAES) systems. The rock mass in A-CAES plants is subjected on a daily base to mechanical cycling loading during the charge and discharge processes. Therefore, it is essential to analyze the behavior of the rock mass for the entire service life. Two different lining options are analyzed, with 15 cm thick concrete lining and unlined tunnels, both with an internal synthetic seal to avoid air leakage through the lining and rock mass fractures. In this paper, two 3D numerical models have been developed to analyze the geomechanical performance of A-CAES plants. In the first model, deformations and plasticity state are studied assuming pressure values of 5, 7.5 and 10 MPa and considering a storage space of 12, 800 m 3 . Then, in the second model, the cycling loading operation is simulated for 10, 000 cycles (service life) for lined and unlined tunnels, considering a pressure range between 4.5 and 7.5 MPa. The results obtained show that the rock mass surrounding the tunnels can resist the pressure with moderate deformations and small thickness of plastic zones, while an increase of the initial volume of less than 0.5% has been observed by applying the operating conditions. In addition, no fatigue failure is expected during the operation time.